1992
DOI: 10.1172/jci115910
|View full text |Cite
|
Sign up to set email alerts
|

Both immunity and hyperresponsiveness to Pneumocystis carinii result from transfer of CD4+ but not CD8+ T cells into severe combined immunodeficiency mice.

Abstract: The opportunistic pathogen Pneumocystis carini (Pc) is considered to be the leading cause of morbidity in patients with AIDS. It is important, therefore, to determine the immunological mechanisms of resistance to Pc. We have taken advantage of the lack of both T and B lymphocytes in severe combined immunodeficiency (scid) mice to determine the critical factors in resistance to spontaneously acquired Pc pneumonia. Invest. 1992.90:673-678.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
131
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 32 publications
12
131
2
Order By: Relevance
“…Consistent with previously published studies (16,17,30,33,39), our studies show that CD4 ϩ T cells are absolutely essential to clear the P. carinii infection. It is possible that features of CD4 function that are essential for P. carinii clearance are also responsible for inflammatory lung injury.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previously published studies (16,17,30,33,39), our studies show that CD4 ϩ T cells are absolutely essential to clear the P. carinii infection. It is possible that features of CD4 function that are essential for P. carinii clearance are also responsible for inflammatory lung injury.…”
Section: Discussionsupporting
confidence: 93%
“…Using a murine model of IRD, the contribution of individual lymphocyte subsets was studied by selective depletion using specific MAb. Our results not only confirmed that CD4 ϩ T cells are critical for P. carinii-clearance (16,30,34,39), but also demonstrated that they directly contribute to the severe lung injury associated with IRD. Furthermore, our results show that CD8 ϩ T cells also play a dual role during PcP: an immune-modulatory role in the presence of CD4 ϩ T cells, and an inflammatory, nonprotective role in the absence of CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations